Diversity and Ideology. Challenges of the Scientific Description of Spanish in Contact with Amerindian Languages - Pfänder, Stefan (2024)
Certain underlying ideologies in society may surface, either consciously or unconsciously, in the linguistic analyses of contact situations. To illustrate this, we present some ideological biases in the treatment of linguistic diversity found in the Nueva gramática de la lengua española (NGLE) and the Diccionario Panhispánico de Dudas (DPD), two significant academic works from 2010 and 2005. We contrast these claims with empirical studies that rigorously analyse Andean Spanish and delve into two types of changes caused by linguistic contact, as well as the attitudes of speakers of the varieties of Spanish described here. We conclude with some final reflections on ideology and the scientific description of linguistic diversity in the Andes.